Application of the scoring system and therapeutic interventions (TISS-28) in post cardiac surgery patients in the intensive care unit of a teaching hospital in western Pará - dos Santos, Luan Gomes; Vieira, Elzo Everton de Sousa; Valente, Antonia Regiane Pereira Duarte (Seven Editora, 2023)
Introduction: An Intensive Care Unit (ICU) is a critical area for the hospitalization of critically ill patients and for the classification of severely ill patients and who use instruments that demonstrate instability and likelihood of their recovery. Objective: To evaluate the use of the TISS-28 score from the direct and indirect observation of postoperative cardiac patients in an ICU. Methods: cross-sectional and prospective study, procedure with descriptive, analytical and quantitative approach performed in the ICU of a teaching hospital in western Pará with patients of both sexes, aged ≥ 18 years, in the postoperative period. cardiac surgery,. Results: females aged 40 to 79 years were the most prevalent and presented comorbidities such as systemic arterial hypertension and / or diabetes mellitus, performing mainly surgeries such as myocardial revascularization and as aortic and mitral valve replacement, where, as the main complications in the Post-cardiac surgery were decreased base vesicular murmurs and tachycardia, with an average ICU stay of 6 days per patient. Conclusions: It is concluded that the application of TISS-28 facilitates the evaluation process of the patient and contributes significantly to the determination of the best conduct of the multidisciplinary team. DOI: https://doi.org/10.56238/colleinternhealthscienv1-022